Analysis of Relationship Between Internet of Things (IoT) Implementation and Digital Marketing Among MSMEs In Selangor - Kirbashini Balakrishnan; Ramasamy, Chandrashekar (Research in Management of Technology and Business, 2024)
The implementation of Internet of Things (IoT) technology has become integral to the digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Selangor. This study explores the dynamic relationship between IoT adoption and digital marketing strategies within this sector. As MSMEs leverage IoT for enhanced operational efficiency, real-time data collection, and process automation, a significant impact on digital marketing practices is observed. The interconnected nature of IoT devices facilitates targeted customer engagement, personalized marketing strategies, and data-driven decision-making. MSMEs in Selangor are increasingly recognizing the symbiotic relationship between IoT implementation and digital marketing, viewing it as a catalyst for competitive advantage and market expansion. The research will use quantitative method to collect data. The population are MSME owners, managers, administrative and staffs. The data collected through the questionnaire will be analysed using Statistical Package for Social Sciences (SPSS) and forecasting techniques.